The Integration Effect of Technical and Psychological Aspects on Occupational Fraud Disclosure - Fauzan, Zulfikar (Goodwood Akuntansi dan Auditing Reviu, 2026)
Purpose: This study aims to examine the influence of investigative audits, professional judgment, and whistleblowing systems on occupational fraud disclosure, with the locus of control as a moderator. Methodology/approach: This study uses a quantitative approach with Partial Least Squares (PLS) analysis. Data were collected through questionnaires distributed to internal auditors who attended professional training at Yayasan Pendidikan Islam Al-Azhar (YPIA) in 2025. Data analysis was performed using SmartPLS 4. Results: Investigative audits (? = 0.332; P = 0.000; t = 10.294), professional judgment (? = 0.336; P = 0.000; t = 10.100), and whistleblowing systems (? = 0.201; P = 0.000; t = 6.630) positively affect occupational fraud disclosure. Locus of control strengthens the effect of professional judgment (? = 0.120; P = 0.007; t = 2.691) and whistleblowing systems (? = 0.079; P = 0.024; t = 2.258) but does not strengthen the effect of investigative audits (? = 0.056; P = 0.117; t = 1.568). Conclusions: This study provides a new theoretical contribution by proving that effective disclosure of occupational fraud is not only determined by technical aspects but is also influenced by individual psychological aspects. Limitations: This research is limited to one professional training institution, the sample used is only internal auditors, and only three independent variables are used. Contributions: The findings of this study contribute to the audit literature and can be used by organizations and internal auditors to improve the effectiveness of fraud disclosure.